MEMPERTIMBANGKAN DASAR ETIS TANGGUNG JAWAB MORALAKUNTAN DARI PERSPEKTIF ETIKA EMMANUEL LEVINAS - Urbanus Ura Weruin; Yuniarwati Yuniarwati (Jurnal Serina Ekonomi dan Bisnis, 2023)
The development of a free market economy that is massive and competitive and the desire to reap hugeprofits instantly has given birth to fraudulent business practices. One of the unethical business practices isthe manipulation of financial reports by accountants. In some cases, public accountants turn loss-makingcompany financial statements into profits. In this case, professional accountants already have a moralumbrella in the form of a code of ethics for the accounting profession as a basic guideline in carrying outaccounting practices. The code of ethics for the accounting profession emphasizes that accountants mustadhere to professional principles such as responsibility, public interest, maintaining integrity, objectivity,increasing competence and professionalism, being independent, applying the precautionary principle,maintaining confidentiality, and must comply with the rules. ethics for the accounting profession. LawNumber 5 of 2011 concerning The Public Accountants also emphasizes that public accountants must behaveproperly, be honest, be responsible, and have high integrity. However, in several major cases in Indonesia,the credibility, integrity, honesty and responsibility of public accountants to the state and the widercommunity have been questioned. Why does this happen so often? This article will analyze philosophicallythe relevance of Emmanuel Levinas's ethical thoughts for the ethical responsibilities of accountants. Theresults of library research using the content analysis method show that for Levinas the ethical-moral basisfor accountants' ethical responsibilities is not something normative-pragmatic but substantial-ontological.The ethical basis of the moral responsibility of accountants is not on the autonomy, freedom,professionalism and competence of accountants as subjects but on the subordination and intersubjectivitybetween the subject and the "Others" (the Others). For Levinas, responsibility towards the "Others" (theOthers) is characterized as ethical, asymmetrical, and absolute.